Studies Of The Antifungal And Anticancer Properties Of Hevea Brasiliensis Latex B-Serum And Their Sub-Fractions - Yang, Kok Lee (2013)
Previous studies using latex B-serum, extracted from the Hevea brasiliensis latex has exhibited its anticancer properties on HeLa cells. This has paved the way further analysis of the anticancer properties on different human cancer cell lines with higher therapeutic index. In this study, toxicity of latex whole B-serum (WB) and its sub-fractions (DBP, DBS, BBP and BBS) was first assessed using brine shrimp lethality test (BSLT). Anticancer properties were assessed using MTT assay where a panel of human cancer-origin cells was applied. Antifungal properties of Hevea brasiliensis latex B-serum was then tested using disc diffusion, minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) assay. Possible cell death mechanism induced by WB and its sub-fractions was studied using DNA fragmentation assay, followed by real-time reverse transcriptase- quantitative polymerase chain reaction (RT-qPCR). Results from BSLT indicated that WB and its sub-fractions have low toxicity level (461.0 mg/ml) according to the classification by Meyer et al., (1982). This result was further confirmed by MTT assay that the Hs27 (non-cancer origin) cell viability was not affected by the treatment of WB and its sub-fractions where the cell viability was remained above 90% at treatment up to 72 hours. Meanwhile, among the six human cancer-origin cell lines tested, HepG2 and MDA-MB231 cell lines showed high susceptibility towards the treatment of WB with the LC50 value 8.657 and 85.86 μg/ml, respectively and DBP with the LC50 value 1.172 and 5.364 μg/ml, respectively. However, no similar effect was observed in BBP and BBS sub-fractions treated cells.